MAMMOGRAPHY - WINNIECIADKHAR; JOSEPH BERNARD; JOSEPH BERNARD (International Journal of Pharma and Bio Sciences, 2013)
Breast cancer is one of the most increasing cancer, it originate mainly from the breast tissue commonly from inner lining of milk duct.or the lobules that supply the ducts with milk. While the overwhelming majority of human cases occur in women, male breast cancer can also occur Worldwide, breast cancer accounts for 22.9% of all cancers in women. In 2008, breast cancer caused 458,503 deaths worldwide (13.7% of cancer deaths in women) There were an estimated 12.7 million cancer cases around the world in 2008, of these 6.6 million cases were in men and 6.0 millions in women .This number is expected to increase to 21 million by 203.This article is to strive to raise awareness about accessibility to screening and to encourage more women to go for mammograms after the age of 40yrs. Educate the people about mammography and its procedure. The screening mammogram is one of the most effective tools available to detect breast cancer early.